SHRIMP zircon U–Pb ages from coal beds across the Permian–Triassic boundary, eastern Yunnan, southwestern China - Wang, Juan; Shao, Long-Yi; Wang, Hao; Spiro, Baruch; Large, David (Elsevier, 2018)
The first SHRIMP zircon U–Pb ages from coal beds close to the end-Permian mass extinction are reported from the C1 coal seam in the Yantang Mine in Laibin Town, Xuanwei County, eastern Yunnan Province. Zircons were extracted from kaolinite claystone layers, defined as tonsteins (volcanic ash deposits), in the sub-seam B1 and B3 of the coal seam C1. The U–Pb ages are 252.0 ± 2.3 Ma and 250.3 ± 2.1 Ma for the sub-seam B1 and B3, respectively. Within analytical uncertainties, these U–Pb ages include the time period of the onset of the mass extinction at 251.941 ± 0.037 Ma, which was obtained from the marine Meishan section in Zhejiang Province, ∼1600 km away from the Yantang Mine. These new ages represent not only the first and closest ages to the PTB mass extinction in terrestrial coal beds, but also ages from the nearest site to the Emeishan volcanoes investigated so far. Therefore these new data provide the most accurate stratigraphic horizon of terrestrial facies of the end-Permian extinction in South China. The Emeishan volcanoes were likely the source of volcanic ash in the coal seams at the Xuanwei County and broader areas in South China. Furthermore, the minerals and geochemistry characteristics of the C1 coal seam also implied the influences of contemporaneous volcanic activities.